STRUCTURE OF PSYCHOLOGICAL HEALTH PERSONALITY OF A TEACHER - Pavlyk, Natalia; Shpak, Denis (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article presents a theoretical analysis of the concepts of «mental health», «psychological health». The importance of psychological health for the teacher's professional activity is outlined. The authors defined the hierarchical structure of the psychological health of a personality. The structure of psychological health has psychosomatic, mental, social and spiritual components.